Analisis Praktik Giveaway Dalam Jual Beli Online pada Perspektif Ekonomi Syariah: Studi pada Oflaila_Busana - Jahro Hasibuan; Sarwo Edy; MH. Ainulyaqin (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The purpose of this study was to find out the giveaway practices carried out by oflaila_busana by buying and selling online from a sharia economic perspective. Currently, the practice of giveaway is widely used by online shops as a sales attraction, so that their products are better known by the wider community. This study uses a qualitative descriptive method by providing explanations and descriptions regarding giveaway buying and selling in the perspective of Islamic economics. Which is done by describing a problem or phenomenon that occurs accurately. And the results obtained are well described. Methods of data collection by means of observation, interviews, and/or document review. The research location is oflaila_busana which uses online media in sales by practicing a giveaway system in sales promotion. The results of this study based on the data obtained indicate that the giveaway held at oflaila_busana does not contain conditions that are prohibited in religion. So the giveaway practice at oflaila_busana is in accordance with the sharia economy. Keywords: giveaway, online media, sharia economy